Immunity in early childhood in the pandemic peroid - Tri Kurniawati; Naili Sa‟ida (Universitas Muhammadiyah Surabaya, 2020)
Abstract.Covid 19 cases are increasing both globally and nationally, so there is a need forprevention from each individual and recovery from eachpatients. Incident cases not only occur in adults but also in children. Cases or patients in children will be more difficult tohandle. Prevention should be done by increasing the body's immune system is good. Improvement of the general system in children can be done by improving consumption patterns that contain macro nutrients and micro nutrients. Vitamins given to early childhood are better derived from foods compared to dietary supplements by regulating consumption patterns and adding variations in types and sources of food ingredients. A good immune system will be able to fight Covid 19 that enters the body thereby reducing the severity and risk of death. In addition to enhancing the immune system, maintaining a clean lifestyle and maintaining a social distance is also important to prevent the spread of Covid 19.